Peranan Kuat Medan Elektromagnetik dalam Memacu Pertumbuhan Vegetatif Tanaman Krisan (Crhysantemum) - Permana, I Gusti Putu Eka; S. Wijaya, I Made Anom; Gunadnya, I.B. Putu (Jurnal BETA (Biosistem dan Teknik Pertanian); Vol 4 No 1 (2016): Maret)
The purposes of this research were to observe the role of electromagnetic field exposure on vegetative phase to spur the growth of Chrysanthemum plants and to determine the appropriate electromagnetic field strength and frequency of exposure that resulted the best growth of chrysantemum plants. The method of this research was descriptive analysis with two treatment. The first treatments was electromagnetic strength consist of 2 mT (B1), 3 mT (B2), and 4 mT (B3). The second treatment was frequency of electromagnetic field exposure, consist of 1 (F1), 2 (F2), and 3 (F3) times per day. In this research, the control was without exposure by electromagnetic field used as a comparision and. Variables measured were phase were root length, rod diameter, plant height, amount of leave, and plant canopy. The result showed that plant which exposured by 2 mT until 3 mT electromagnetic field 2 times per day had a good impact for vegetative growth, however for more than 3 mT, gave unstatisfactory impact. Plant with the best vegetative growth results were exposured by 3 mT electromagnetic field 2 times per day or B2F2
Keywords: electromagnetic field , vegetative growth, chrysanthemum plants